x2 + 2x – 3
= x2 + 2x + 1 – 4
= (x + 1)2 – 22
= (x + 1 + 2)(x + 1 – 2)
= (x + 3)(x – 1)
x2 + 2x – 3
= x2 + 2x + 1 – 4
= (x + 1)2 – 22
= (x + 1 + 2)(x + 1 – 2)
= (x + 3)(x – 1)
phân tích các đa thức sau thành nhân tử: x2+2x-3
Phân tích đa thức sau thành nhân tử :
a,x4+8x+63
b,(x5+4)+(x3+4)-16
c,(x2+2x+7)+(x2-2x+4)(x2+2x+3)
Phân tích các đa thức sau thành nhân tử: x 2 + 2 x - 15 y 2
Phân tích các đa thức sau thành nhân tử x 2 - 2 x - 4 y 2 - 4 y
Phân tích các đa thức sau thành nhân tử: x2 + 2x – y2 + 1
Phân tích các đa thức sau thành nhân tử x 2 - 2 x - 4 y 2 - 4 y
Phân tích đa thức sau thành nhân tử: 2x – 2y – x2 + 2xy – y2
phân tích đa thức sau thành nhân tử
2x3-5xx2x2+6x-15
phân tích đa thức sau thành nhân tử
a) (x+2)(x2-2x+1)